`A=-x^2+2x+10`
`=-(x^2-2x)+10`
`=-(x-1)^2+11<=11`
Dấu "=" xảy ra khi `x=1`.
`B=4x-2x^2+8`
`=-2(x^2-2x)+8`
`=-2(x^2-2x+1)+10`
`=-2(x-1)^2+10<=10`
Dấu "=" xảy ra khi `x=1`
`C=-x^2-x+1`
`=-(x^2+x)+1`
`=-(x^2+x+1/4)+1+1/4`
`=-(x+1/2)^2+5/4<=5/4`
Dấu "=" xảy ra khi `x=-1/2`
`D=-4x^2+6x+3`
`=-(4x^2-6x)+3`
`=-(4x^2-6x+9/4)+21/4`
`=-(2x-3/2)^2+21/4<=21/4`
Dấu "=' xảy ra khi `2x=3/2<=>x=3/4`
\(a,A=-x^2+2x+10=-x^2+2x-1+11=-\left(x^2-2x+1\right)+11\)
\(=11-\left(x-1\right)^2\)
- Thấy : \(\left(x-1\right)^2\ge0\forall x\in R\)
\(\Rightarrow A=11-\left(x-1\right)^2\le11\)
Vậy MaxA = 11 <=> x = 1 .
\(b,B=-2x^2+4x-2+10=-2\left(x^2-2x+1\right)+10=10-2\left(x-1\right)^2\)
- Thấy : \(\left(x-1\right)^2\ge0\forall x\in R\)
\(\Rightarrow B=10-2\left(x-1\right)^2\le10\)
Vậy MaxB = 10 <=> x = 1 .
\(c,C=-x^2-\dfrac{1}{2}.2.x-\dfrac{1}{4}+\dfrac{5}{4}=\dfrac{5}{4}-\left(x+\dfrac{1}{2}\right)^2\)
- Thấy : \(\left(x+\dfrac{1}{2}\right)^2\ge0\forall x\in R\)
\(\Rightarrow C=\dfrac{5}{4}-\left(x+\dfrac{1}{2}\right)^2\le\dfrac{5}{4}\)
Vậy MaxC = 5/4 <=> x = -1/2 .
\(d,D=-4x^2+6x+3=-4x^2+2x.2.\dfrac{6}{4}-\dfrac{9}{4}+\dfrac{21}{4}=-\left(4x^2-6x+\dfrac{9}{4}\right)+\dfrac{21}{4}\)
\(=\dfrac{21}{4}-\left(2x-\dfrac{3}{2}\right)^2\)
- Thấy : \(\left(2x-\dfrac{3}{2}\right)^2\ge0\forall x\in R\)
\(\Rightarrow A=\dfrac{21}{4}-\left(2x-\dfrac{3}{2}\right)^2\le\dfrac{21}{4}\)
Vậy MaxD=21/4 <=> x = 3/4 .